2018
DOI: 10.3390/toxins10080324
|View full text |Cite
|
Sign up to set email alerts
|

Human Poisoning from Marine Toxins: Unknowns for Optimal Consumer Protection

Abstract: Marine biotoxins are produced by aquatic microorganisms and accumulate in shellfish or finfish following the food web. These toxins usually reach human consumers by ingestion of contaminated seafood, although other exposure routes like inhalation or contact have also been reported and may cause serious illness. This review shows the current data regarding the symptoms of acute intoxication for several toxin classes, including paralytic toxins, amnesic toxins, ciguatoxins, brevetoxins, tetrodotoxins, diarrheic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 234 publications
(384 reference statements)
1
80
0
3
Order By: Relevance
“…OA, DTX-1 and DTX-2 are lipophilic toxins produced by dinoflagellates with different levels of toxicity; also, they are the main compounds associated with episodes of DSP [16]. The cell viability results obtained using the MTT assay showed that DTX-2 is less toxic than OA and DTX-1 when the values of IC50 were compared; this is in line with what has been reported previously, where OA and DTX-1 are considered to be equally toxic, while DTX-2 is almost 40% less toxic [17]. However, other studies have reported that DTX-1 is more toxic than OA and DTX-2 [9].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…OA, DTX-1 and DTX-2 are lipophilic toxins produced by dinoflagellates with different levels of toxicity; also, they are the main compounds associated with episodes of DSP [16]. The cell viability results obtained using the MTT assay showed that DTX-2 is less toxic than OA and DTX-1 when the values of IC50 were compared; this is in line with what has been reported previously, where OA and DTX-1 are considered to be equally toxic, while DTX-2 is almost 40% less toxic [17]. However, other studies have reported that DTX-1 is more toxic than OA and DTX-2 [9].…”
Section: Discussionsupporting
confidence: 89%
“…Toxins from DSP are potent inhibitors of PP2A and to a lesser extent of PP1, which are the most abundant protein phosphatases in cells [12]. Protein phosphatases modulate a large number of cell signaling pathways such as proliferation, differentiation and apoptosis [17]. Due to the above, in this study, PP2A activity was evaluated in the three cell lines after treatment with marine toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most importantly, many of these approaches have dramatically reduced the amount of starting material required for analysis. Many previously uncharacterised toxin-containing samples (e.g., venoms of small invertebrate species, aquatic toxins produced by marine and freshwater algae or bacteria) are now amenable for compositional and functional characterisation [31][32][33]. Consequently, several companies now provide libraries of diverse toxins for pharmaceutical screening purposes, and thus toxins remain interesting targets for therapeutic and diagnostic translation [8].…”
Section: Glossarymentioning
confidence: 99%
“…Among the cyanotoxins, paralytic shellfish poisoning (PSP) toxins and microcystins (MCs) are two toxin groups encompassing the highest number of toxic structural variants. PSP toxins are chemically related neurotoxins comprising up to 58 congeners with saxitoxin (STX) being the most toxic one [1]. Most of the PSP poisoning events have been reported from the consumption of marine-derived seafood which can even contain lethal concentrations of PSP toxins [2], whereas intoxications caused by MCs are a result of contaminated drinking water [3].…”
Section: Introductionmentioning
confidence: 99%